2015
DOI: 10.1155/2015/359130
|View full text |Cite
|
Sign up to set email alerts
|

The Demographic and Clinical Characteristics of Ulcerative Colitis in a Northeast Brazilian Population

Abstract: Introduction. The purpose of this study was to describe the clinical and demographic characteristics of UC in Bahia, a Brazilian state, and to identify the variables associated with extensive colitis, steroid therapy, immunosuppression, and colectomy. Methods. In this cross-sectional study UC patients were interviewed, and additional information was collected from the medical records. Descriptive statistics and multivariate Poisson regression analysis were used. Results. This study included 267 individuals, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 34 publications
7
37
1
8
Order By: Relevance
“…In the group of patients with UC, there was a tendency toward an increase in incidence among patients over 60 years old. Such results are indistinct from the ones obtained in other Brazilian studies, such as those by Silva and Souza et al, and international studies, such as those by Burisch and Munkholm and Chouraki et al 8 , 14 , 19 , 23 We admit, however, that delay in the diagnosis of IBD can influence the outcome of the incidence distribution by age groups. In a recent study undertaken in the Northeast region of Brazil, a delay of up to 28.2 months was observed between the beginning of the clinical manifestations and the diagnostic confirmation of IBD.…”
Section: Discussionsupporting
confidence: 56%
“…In the group of patients with UC, there was a tendency toward an increase in incidence among patients over 60 years old. Such results are indistinct from the ones obtained in other Brazilian studies, such as those by Silva and Souza et al, and international studies, such as those by Burisch and Munkholm and Chouraki et al 8 , 14 , 19 , 23 We admit, however, that delay in the diagnosis of IBD can influence the outcome of the incidence distribution by age groups. In a recent study undertaken in the Northeast region of Brazil, a delay of up to 28.2 months was observed between the beginning of the clinical manifestations and the diagnostic confirmation of IBD.…”
Section: Discussionsupporting
confidence: 56%
“…High hospitalisation rates were reported in Bahia, Brazil and Santiago, Chile, with 43.8% and 34.6% of patients requiring hospitalisation, respectively. 16 , 24 Colectomy rates varied between countries, with 22% of patients in Puerto Rico, 10.5% in Montevideo, Uruguay, 10.1% in Mexico City and 1.5–3.4% in Bahia, Brazil requiring a colectomy. 16 , 17 , 29 , 34 , 36 In Montevideo, Uruguay, 5.0% of patients underwent proctocolectomy (3.8% pouch and 1.3% definitive ileostomy) and 4.2% of patients required a colectomy.…”
Section: Resultsmentioning
confidence: 99%
“…[50]One study found a higher prevalence of left-sided colitis, higher mortality, and higher usage of biological agents in Mexican population than in Mexican-American population, supporting the role of environmental factors on clinical characteristics of IBD. [24] The larger case-series in LAC Countries are from 1946 to date are from Argentina [14,51,52], Barbados [13], Brazil [14,[53][54][55][56][57][58][59][60][61][62][63][64][65], Chile [66][67][68], Cuba [69], Peru [70,71], Puerto Rico [72][73][74][75] and Uruguay. [76][77][78] Most CD localizations were ileal-colonic and CD behavior was mostly inflammatory, followed by penetrant or stenotic.…”
Section: Discussionmentioning
confidence: 99%